Participatory Plant Breeding: A New Challenge in the Generation and Appropriation of Potato Varieties by Farmers in Bolivia - Gabriel, J.; Herbas, J; Salazar, M.; Ruíz, J.; López, J.; Villarroel, J; Cossio, D (CGIAR System Organization, 2004)
Experiments on participatory plant breeding were carried out with the active participation of farmers from the Morochata Region in Bolivia.